2023
DOI: 10.1186/s12883-023-03158-x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear relationship between glycated hemoglobin and cognitive impairment after acute mild ischemic stroke

Abstract: Background Stroke is the second most common cause of morbidity and mortality. Even mild stroke survivors have an increased risk of cognitive impairment. Studies have been conducted on the relationship between glycated hemoglobin (HbA1c) and cognitive decline, but the findings have been inconsistent. Therefore, this study examined the link between HbA1c levels and cognitive impairment following acute mild ischemic stroke. Methods Data from 311 patie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…It was confirmed that the HbA1c value was inversely correlated with various measures of cognitive condition; thus, high levels of blood glucose were verified as a major risk factor for cognitive impairment [25]. Interestingly, a nationwide, register-based cohort with all diabetes cases conducted by Andersen and co-workers in Denmark from January 2000 through December 2012 (n > 150,000) revealed that high HbA1c levels were correlated with lessened cognitive performance [26]. Another study of 311 patients (aged 23 to 96 years old) with acute mild ischemic stroke at the Suining Central Hospital, Sichuan Province, China, from 1 January 2015 to 31 December 2018, demonstrated almost similar results.…”
Section: Discussionmentioning
confidence: 84%
“…It was confirmed that the HbA1c value was inversely correlated with various measures of cognitive condition; thus, high levels of blood glucose were verified as a major risk factor for cognitive impairment [25]. Interestingly, a nationwide, register-based cohort with all diabetes cases conducted by Andersen and co-workers in Denmark from January 2000 through December 2012 (n > 150,000) revealed that high HbA1c levels were correlated with lessened cognitive performance [26]. Another study of 311 patients (aged 23 to 96 years old) with acute mild ischemic stroke at the Suining Central Hospital, Sichuan Province, China, from 1 January 2015 to 31 December 2018, demonstrated almost similar results.…”
Section: Discussionmentioning
confidence: 84%
“…Post-stroke DM is associated with post-stroke cognitive decline and dementia [38,57]. A recent study suggests a potential non-linear relationship between hemoglobin A1C and post-stroke cognitive impairment [58]. However, it remains unclear if improvement in hemoglobin A1C following stroke independently improves post-stroke cognitive and functional outcomes and what, if any, is the ideal target hemoglobin A1C to mitigate the risk of post-stroke dementia.…”
Section: Diabetes and Glycemic Impairmentmentioning
confidence: 99%